bahasa Inggris - Harini, Harini; Maharsi, Ista (Journal Of Education And Teaching Learning (JETL), 2025)
Teachers’ beliefs facilitate students’ learning and shape their future professional endeavors. Although many studies have investigated teacher's beliefs in teaching, how pre-service teachers' beliefs were reflected in their teaching practicum still needs to be explored. This study aims to describe how pre-service teachers implement their teaching beliefs during their teaching practicum in a vocational high school. One female pre-service teacher, aged 22 years old, participated in this study. Data were collected from a semi-structured interview. Data were analyzed inductively following Braun and Clark’s thematic analysis. This study has four findings. First, the pre-service teachers believe that students are responsible for educating students, encompassing professional, social, and personal aspects. Teachers must deliver curriculum-appropriate material and ensure the content is relevant to students' interests and future career aspirations, especially in vocational schools. Secondly, the pre-service teachers believe that teachers can assess students' performance through rewards to enhance students’ talent and integrate the assessment into their learning experience. Thirdly, pre-service teachers believe that teachers play roles in the classroom as mentors and authority figures who create a supportive and engaging learning environment while maintaining control and discipline. Fourth, the linearity of learning assessments and activities can evolve to suit learning assessments and activities to the developmental needs of students who may struggle with them. Pre-service teachers’ beliefs can help create a more meaningful learning and engaging educational environment that promotes students’ academic success.